ChemInform Abstract: Magnetic Ordering in the Pyrochlore Ho2CrSbO7 Determined from Neutron Diffraction, and the Magnetic Properties of Other RE2CrSbO7 Phases (RE: Y, Tb, Dy, Er). Issue 31 (5th August 2014) - Whitaker, Mariana J.; Greaves, Colin
Abstract Ho2CrSbO7 is found to form an "ordered spin‐ice structure" below 13 K where the magnetic moments are constrained along the 111 axes, but with a ferromagnetic moment in one direction.